The role of a trustee in Sukuk: the Malaysian perspective - Hassan, Rusni; Mat Yaman, Khariyah; Othman, Ahmad Azam; Yusoff, Adnan (INSI Publications, 2012)
In Malaysia, the legal and regulatory framework governing Islamic Capital Market industry provides for trust structure insukuk. Trustee plays an important role in sukuk. In fact in everysukuk issuance save for the issue or offer which comes under the exceptions provided for under Schedule 8 of the Capital Market Services Act 2007 (“CMSA”), a trustee is required to be appointed and a trust deed to be executed. Thus, trust structure is central in sukuk, so far as Malaysia is concerned. This paper studies the important roles of trustees in sukuk, its nature and the extent of powers and duties of trustees appointed therein. Itexamines the categories of trustees in sukuk and their designated functions as well the nature and extent of powers and duties of a trustee with an insight on the current practices in the Malaysian Islamic Capital Market industry dealing with trust structure insukuk. The study will also look at other relevant aspects in trust structure, which include the trust deed as the constitutive document and the role of trustee in the event of default of sukuk.